An enhanced ball grid array packaging process
By forming a composite adhesive layer of filler layer, intermediate adhesive layer and brown polyimide tape on the gold-plated surface of the substrate material copper block, the problem of unsolid adhesive tape caused by gaps on the surface of the gold-plated layer is solved, and a packaging process with high peel strength and overall peelability is achieved.
Patent Information
- Application Number
- CN202411849090.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-12-16
AI Technical Summary
Since there are a large number of voids on the surface of the gold-plated layer on the copper block in the substrate, the high-temperature-resistant brown polyimide tape is not firmly bonded to the surface of the gold-plated layer, and it is easy to fall off or displace.
The composite adhesive layer formed by a filler layer, an intermediate adhesive layer and a high-temperature-resistant brown polyimide tape are used to protect the gold-plated surface of the copper block in the substrate. The filler layer is prepared by materials such as gelatin powder and polyurethane, and the intermediate adhesive layer is prepared by materials such as photosensitive prepolymers and modified cellulose to form a composite adhesive layer that is peelable and has high adhesive strength.
The high peel strength between the composite adhesive layer and the gold-plated surface of the copper block in the substrate is achieved, avoiding the problem of tape falling off or displacement, and ensuring the overall peelability of the composite adhesive layer.
Smart Images

Figure CN119314912B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electronic packaging and relates to an enhanced ball grid array packaging process. Background Art
[0002] Enhanced ball grid array (BGA) packaging technology belongs to the field of electronic packaging technology. BGA packaging technology is a surface mount packaging technology used on integrated circuits. It is usually used to permanently fix devices such as microprocessors. This packaging technology can provide more pins than other packaging forms (such as dual in-line packages or quad flat packages), and the entire bottom surface of the device can be used as pins, resulting in shorter average wire length and better high-speed performance.
[0003] In the enhanced ball grid array packaging process, in order to prevent the gold-plated layer on the surface of the copper block of the substrate from being scratched during the subsequent packaging process, a high-temperature resistant brown polyimide tape with a polyimide film as the base material and coated with silicone pressure-sensitive adhesive on one side is generally attached to the surface of the gold-plated layer on the surface of the copper block of the substrate for protection; although the brown polyimide tape has high-temperature resistance and can be peeled off without residual adhesive after peeling; however, since there are a large number of pores on the surface of the gold-plated layer on the surface of the copper block of the substrate, after the high-temperature resistant brown polyimide tape is pressed and attached to the surface of the gold-plated layer on the surface of the copper block of the substrate, a large number of tiny bubbles will exist between the tape and the gold-plated layer, making the bonding between the tape and the gold-plated layer not firm, and the tape is easy to fall off or move during subsequent operations. Summary of the invention
[0004] The purpose of the present invention is to provide an enhanced ball grid array packaging process, which solves the problem that a large number of gaps exist on the surface of the gold-plated layer on the surface of the copper block of the substrate material, so that the high-temperature resistant brown polyimide tape is not firmly bonded to the surface of the gold-plated layer, and the tape is easy to fall off or move.
[0005] The technical solution adopted by the present invention is as follows:
[0006] An enhanced ball grid array packaging process includes performing protective treatment on the gold-plated surface of a copper block of a substrate material, wherein the protective treatment on the gold-plated surface of the copper block of the substrate material is achieved by the following specific steps:
[0007] S1. Clean the gold-plated surface of the incoming copper block of the substrate;
[0008] S2. A composite adhesive layer formed by a filler layer, an intermediate adhesive layer, and a high-temperature resistant brown polyimide tape is used to protect the gold-plated surface of the copper block of the substrate after the dust removal treatment. The specific steps are as follows:
[0009] S2.1, preparing a filler layer: using 60-65 parts of gelatin powder, 20-22 parts of polyurethane, 5-6 parts of low-density polyethylene, 8-10 parts of nano inorganic filler, 2-3 parts of light stabilizer, and 3-5 parts of dispersant as main raw materials to prepare a filler layer that adheres to the gold-plated surface of the copper block of the substrate and can be peeled off, and the filler layer performs a leveling treatment on the surface of the gold-plated layer by filling the pores on the surface of the gold-plated layer;
[0010] S2.2, preparing an intermediate adhesive layer: using 50-55 parts of photosensitive prepolymer, 20-30 parts of modified cellulose, 5-6 parts of titanate coupling agent, active diluent and photosensitizer matching the photosensitive prepolymer as main raw materials to prepare an intermediate adhesive layer adhered to the surface of the filler layer, wherein the photosensitizer is 4% of the mass of the photosensitive prepolymer;
[0011] S2.3. First spray a filler layer on the gold-plated surface of the copper block of the substrate material. After air-drying at room temperature for 10 minutes, spray an intermediate adhesive layer on the surface of the filler layer. Then use a 200W ultraviolet lamp with a wavelength of 365nm to irradiate the intermediate adhesive layer for 6 minutes. After 6 minutes, press and adhere the high-temperature resistant brown polyimide tape to the intermediate adhesive layer. Continue to air-dry at room temperature for 30-40 minutes. The filler layer, the intermediate adhesive layer, and the high-temperature resistant brown polyimide tape are sequentially adhered to form a composite adhesive layer to complete the protective treatment of the gold-plated surface of the copper block of the substrate material.
[0012] The present invention first sprays a filler layer on the surface of the gold-plated layer. The filler layer uses gelatin powder as a main material to achieve that the filler layer and the surface of the gold-plated layer can be peeled off and there is no residual glue after peeling. Although the coating formed by the gelatin powder can be peeled off, the bonding strength between the coating formed by the gelatin powder and the metal surface is low. Therefore, the present invention adds polyurethane, which can strengthen the bonding strength between the filler layer and the metal surface, and the filler layer added with polyurethane is still peelable and there is no residual glue after peeling. On the basis of the above, the present invention adds low-density polyethylene, nano-inorganic fillers, light stabilizers, and dispersants into the filler layer. The low-density polyethylene Olefins have good film-forming properties and can form a dense protective film, thereby improving the density of the filler layer. Nano-inorganic fillers are evenly distributed in the slurry formed by gelatin powder, polyurethane, and low-density polyethylene under the action of dispersants. After being sprayed on the surface of the gold-plated layer, the nano-inorganic fillers can block the pores on the surface of the gold-plated layer, thereby filling the pores and making the surface of the gold-plated layer smoother. Light stabilizers are used to reduce the light resistance of ultraviolet light to the filler layer. The filler layer covers the surface of the gold-plated layer and has an anti-ultraviolet light effect on the gold-plated layer. This is to avoid the influence of ultraviolet light on the gold-plated layer or the filler layer during the ultraviolet light curing of the intermediate adhesive layer.
[0013] In the present invention, the filler layer is added with low-density polyethylene, which increases the inertness of the filler layer. Although it can avoid the reaction between the filler layer and the gold-plated layer, it also reduces the bonding strength between the filler layer and other materials. If the high-temperature resistant brown polyimide tape is directly pressed and attached to the filler layer, the peeling strength between the tape and the filler layer is low, even less than the peeling strength of the filler layer on the gold-plated layer. When the entire composite adhesive layer is torn off, the tape and the filler layer will not be torn off together. After the tape is torn off, the filler layer will remain on the gold-plated layer, and the filler layer needs to be torn off again. Therefore, the present invention adds a photocatalytically cured adhesive between the filler layer and the high-temperature resistant brown polyimide tape. The adhesive is an intermediate adhesive layer. The adhesive uses a photosensitive prepolymer as a main substance. The mixture of polymer, active diluent, photosensitizer and titanate coupling agent has a fast curing speed under ultraviolet light, and reaches a state of not being fully cured and having a certain degree of stickiness within a few minutes. In this state, when the high-temperature resistant brown polyimide tape is pressed, the middle adhesive layer will not overflow adhesive to the surrounding areas; in addition, the present invention adds modified cellulose to the middle adhesive layer, and the modification of cellulose increases the number and types of functional groups in cellulose, improves the activity of cellulose, and makes it easy for cellulose to react chemically with other materials. The active sites of the adhesive added with modified cellulose will also increase, and the adsorption capacity between the active sites and other materials will be relatively enhanced. The addition of modified cellulose strengthens the bonding strength between the middle adhesive layer and the tape and the filler layer. The cellulose used in the present invention is generally amphoteric modified cellulose. The filler layer and the middle adhesive layer in the present invention have a certain flexibility, which is suitable for the overall bending peeling of the composite adhesive layer.
[0014] The present invention ensures that the composite adhesive layer can be peeled off as a whole, so that the composite adhesive layer and the gold-plated surface of the copper block of the substrate material have a higher peeling strength, and can prevent the composite adhesive layer from falling off. Therefore, the present invention adopts the composite adhesive layer to replace the existing single high-temperature resistant brown polyimide tape, and solves the problem that the high-temperature resistant brown polyimide tape is not firmly bonded to the surface of the gold-plated layer due to a large number of gaps on the surface of the gold-plated layer on the surface of the copper block of the substrate material.
[0015] Furthermore, the preparation method of the modified cellulose is:
[0016] A. placing plant cellulose in a 10% by mass sodium hydroxide solution for alkalization for 5 hours to obtain alkalized cellulose, and then drying the alkalized cellulose in an oven at 65° C. for 10 hours and then grinding the cellulose to obtain cellulose powder;
[0017] B. Add cellulose powder to deionized water, pass nitrogen protection, heat to 40°C and stir at constant temperature for 20 minutes, then add ammonium persulfate (1% by weight of cellulose powder), continue to heat under stirring, and slowly drip N,N,N-trimethyl-3-(2-methylallylamino)-1-propylammonium chloride after heating to 50°C. After stirring at constant temperature of 50°C for 3.5 hours, adjust the pH of the product to neutral, and then filter, wash and dry to obtain the first intermediate product; wherein the mass ratio of N,N,N-trimethyl-3-(2-methylallylamino)-1-propylammonium chloride to cellulose powder is 1:1.5;
[0018] C. Add the first intermediate product to a 5% by mass sodium hydroxide solution, mix evenly, heat to 50°C, slowly add N,N-dimethylacrylamide at 50°C, continue stirring, heat to 60°C, and stir at a constant temperature for 2 hours. After 2 hours, add itaconic acid and sodium allyl sulfonate and continue stirring, keep the temperature of the reaction system at 60°C, continue stirring for 30 minutes, slowly add ammonium cerium nitrate and potassium permanganate composite chain initiator, continue stirring at 60°C for 5 hours, and then cool, filter, wash and dry to obtain modified cellulose; wherein the mass ratio of N,N-dimethylacrylamide to cellulose powder is 1:1, the mass ratio of itaconic acid to cellulose powder is 1:3, and the mass ratio of sodium allyl sulfonate to cellulose powder is 1:1.5.
[0019] The invention relates to a novel amphiphilic modified cellulose. The modified cellulose obtained by modifying cellulose with N,N,N-trimethyl-3-(2-methylallylamino)-1-propylammonium chloride, N,N-dimethylacrylamide, itaconic acid and sodium allyl sulfonate can significantly improve the wettability of an intermediate adhesive layer. The higher the wettability of the intermediate adhesive layer, the more uniform the distribution of the intermediate adhesive layer between a filler layer and a high-temperature resistant brown polyimide tape is, so that the intermediate adhesive layer can be ensured to form a uniform bonding force between the filler layer and the tape surface, thereby improving the bonding strength.
[0020] Furthermore, the photosensitive prepolymer includes epoxy soybean oil-based photosensitive prepolymer, trifunctional polyurethane acrylate, and hexafunctional polyurethane acrylate, and the mass ratio of the epoxy soybean oil-based photosensitive prepolymer, trifunctional polyurethane acrylate, and hexafunctional polyurethane acrylate is 1.5:0.5:1;
[0021] The photosensitizer is 1-hydroxycyclohexyl benzophenone and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, and the mass ratio of 1-hydroxycyclohexyl benzophenone and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide is 2:1;
[0022] The active diluent is polyethylene glycol diacrylate.
[0023] The trifunctional polyurethane acrylate has a fast curing speed, the hexafunctional polyurethane acrylate has high stability, and the epoxy soybean oil-based photosensitive prepolymer has good adhesion. Therefore, the present invention compounded the three to obtain a photosensitive prepolymer with a fast light curing speed, strong adhesion and good flexibility.
[0024] Furthermore, the preparation method of the intermediate adhesive layer is: add a photosensitive prepolymer, an active diluent, a titanate coupling agent and a photosensitizer into a mixer, and stir continuously for 3 hours at 40-45°C to obtain a first mixture, which is taken out for use; take another mixer, add modified cellulose and N,N-dimethylformamide into the mixer, mix and stir, and heat to 80°C, and stir and react continuously at 80°C for 2 hours to obtain a second mixture; the first mixture and the second mixture are mixed to obtain an intermediate adhesive, the intermediate adhesive is evenly sprayed on the filler layer and adhered with a high-temperature resistant brown polyimide tape, and the intermediate adhesive layer is formed after the intermediate adhesive is cured, and the peel strength between the high-temperature resistant brown polyimide tape and the intermediate adhesive layer, and the peel strength between the intermediate adhesive layer and the filler layer are both higher than the peel strength of the filler layer on the gold-plated layer.
[0025] Furthermore, the nano inorganic filler in the filler layer is nano silicon dioxide, the light stabilizer is nano titanium dioxide, and the dispersant is sodium dodecyl sulfate.
[0026] Furthermore, the preparation method of the filler layer is as follows: adding gelatin powder to 50% alcohol by mass and soaking it for 5 minutes, then heating the gelatin powder in a water bath at 50°C to obtain a first liquid; heating polyurethane to 200-230°C, and stirring it for 10-15 minutes to obtain a second liquid; slowly heating low-density polyethylene to 120-140°C, and obtaining a third liquid after it is fully melted; at 60°C, uniformly mixing the first liquid, the second liquid, and the third liquid to obtain a mixture; at 30°C, adding nano-inorganic fillers, light stabilizers, and dispersants to the mixture, dispersing it at a high speed at 5000 rpm for 10 minutes to obtain a filler layer slurry, and uniformly spraying the filler layer slurry on the gold-plated surface of the incoming copper block of the substrate to form a filler layer.
[0027] Furthermore, the thickness of the filler layer after curing is 0.1 mm.
[0028] Furthermore, the heat-resistant brown polyimide adhesive is a heat-resistant brown polyimide tape with a polyimide film as a substrate and coated with a silicone pressure-sensitive adhesive on one side, wherein the silicone pressure-sensitive adhesive is bonded to the middle adhesive layer.
[0029] Furthermore, the plant cellulose includes cotton cellulose, flax cellulose and ramie cellulose in a mass ratio of 3:1:1.
[0030] Furthermore, the mass ratio of ammonium cerium nitrate to potassium permanganate in the ammonium cerium nitrate and potassium permanganate composite chain initiator is 4:1.
[0031] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:
[0032] 1. An enhanced ball grid array packaging process uses a peelable filler layer to first level the surface of the gold-plated layer on the surface of the copper block of the substrate material, so that the gold-plated layer on the surface of the copper block of the substrate material is flat and has a low void ratio, and then uses an intermediate adhesive layer to tightly bond the high-temperature resistant brown polyimide tape to the surface of the filler layer. Compared with the prior art, the entire composite adhesive layer can be peeled off and the high-temperature resistant brown polyimide tape can be prevented from being separated or displaced from the gold-plated layer.
[0033] 2. The peel strength between the high temperature resistant brown polyimide tape and the middle adhesive layer, and the peel strength between the middle adhesive layer and the filler layer in the present invention are both higher than the peel strength of the filler layer on the gold-plated layer, and the entire composite adhesive layer can be removed from the gold-plated layer at one time, with substantially no residual adhesive on the gold-plated layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. It should be understood that the following drawings only illustrate certain embodiments of the present invention and should not be regarded as limiting the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative work, among which:
[0035] Figure 1 is a SEM image of the gold-plated surface of the copper block of the substrate material in Example 1 of the present invention after the gold-plated surface of the copper block of the substrate material is cleaned and not treated with a composite adhesive layer;
[0036] Figure 2 This is a SEM image of the gold-plated surface of the substrate copper block whose gold-plated surface is sprayed with the above-mentioned filler layer in Example 1 of the present invention. DETAILED DESCRIPTION
[0037] In order to make the purpose, technical scheme and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention, that is, the embodiments described are only part of the embodiments of the present invention, rather than all of the embodiments. The components of the embodiments of the present invention described and shown in the drawings herein can be arranged and designed in various different configurations.
[0038] Therefore, the following detailed description of the embodiments of the present invention provided in the accompanying drawings is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without making creative work are within the scope of protection of the present invention.
[0039] It should be noted that relational terms such as "first" and "second" are used only to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.
[0040] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0041] Example 1
[0042] A preferred embodiment of the present invention provides an enhanced ball grid array packaging process, comprising performing a protective treatment on the gold-plated surface of a copper block of a substrate material, wherein the protective treatment on the gold-plated surface of the copper block of the substrate material is achieved by the following specific steps:
[0043] S1. Clean the gold-plated surface of the incoming copper block of the substrate;
[0044] S2. A composite adhesive layer formed by a filler layer, an intermediate adhesive layer, and a high-temperature resistant brown polyimide tape is used to protect the gold-plated surface of the copper block of the substrate after the dust removal treatment. The specific steps are as follows:
[0045] S2.1, preparing a filler layer: using 60 parts of gelatin powder, 20 parts of polyurethane, 5 parts of low-density polyethylene, 8 parts of nano inorganic fillers, 2 parts of light stabilizers, and 3 parts of dispersants as main raw materials to prepare a filler layer that adheres to the gold-plated surface of the copper block of the substrate and can be peeled off, and the filler layer performs a leveling treatment on the surface of the gold-plated layer by filling the pores on the surface of the gold-plated layer; the nano inorganic filler in the filler layer is nano silicon dioxide, the light stabilizer is nano titanium dioxide, and the dispersant is sodium dodecyl sulfate;
[0046] S2.2, prepare the intermediate adhesive layer: use 50 parts of photosensitive prepolymer, 20 parts of modified cellulose, 5 parts of titanate coupling agent, active diluent and photosensitizer matching the photosensitive prepolymer as main raw materials to prepare the intermediate adhesive layer adhered to the surface of the filler layer, wherein the photosensitizer is 4% of the mass of the photosensitive prepolymer; the photosensitive prepolymer includes epoxy soybean oil-based photosensitive prepolymer, trifunctional polyurethane acrylate, hexafunctional polyurethane acrylate, and the mass ratio of the epoxy soybean oil-based photosensitive prepolymer, trifunctional polyurethane acrylate, and hexafunctional polyurethane acrylate is 1.5:0.5:1; the photosensitizer is 1-hydroxycyclohexyl benzophenone and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, and the mass ratio of 1-hydroxycyclohexyl benzophenone and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide is 2:1; the active diluent is polyethylene glycol diacrylate;
[0047] S2.3. First spray a filler layer on the gold-plated surface of the copper block of the substrate material. After air-drying at room temperature for 10 minutes, spray an intermediate adhesive layer on the surface of the filler layer. Then use a 200W ultraviolet lamp with a wavelength of 365nm to irradiate the intermediate adhesive layer for 6 minutes. After 6 minutes, press and adhere the high-temperature resistant brown polyimide tape to the intermediate adhesive layer. Continue to air-dry at room temperature for 40 minutes. The filler layer, the intermediate adhesive layer, and the high-temperature resistant brown polyimide tape are sequentially adhered to form a composite adhesive layer to complete the protective treatment of the gold-plated surface of the copper block of the substrate material.
[0048] The preparation method of the modified cellulose is:
[0049] A. placing plant cellulose in a 10% by mass sodium hydroxide solution for alkalization for 5 hours to obtain alkalized cellulose, and then drying the alkalized cellulose in an oven at 65° C. for 10 hours and then grinding the cellulose to obtain cellulose powder;
[0050] B. Add cellulose powder to deionized water, pass nitrogen protection, heat to 40°C and stir at constant temperature for 20 minutes, then add ammonium persulfate (1% by weight of cellulose powder), continue to heat under stirring, and slowly drip N,N,N-trimethyl-3-(2-methylallylamino)-1-propylammonium chloride after heating to 50°C. After stirring at constant temperature of 50°C for 3.5 hours, adjust the pH of the product to neutral, and then filter, wash and dry to obtain the first intermediate product; wherein the mass ratio of N,N,N-trimethyl-3-(2-methylallylamino)-1-propylammonium chloride to cellulose powder is 1:1.5;
[0051] C. Add the first intermediate product to a 5% by mass sodium hydroxide solution, mix evenly, heat to 50°C, slowly add N,N-dimethylacrylamide at 50°C, continue stirring, heat to 60°C, and stir at a constant temperature for 2 hours. After 2 hours, add itaconic acid and sodium allyl sulfonate and continue stirring, keep the temperature of the reaction system at 60°C, continue stirring for 30 minutes, slowly add ammonium cerium nitrate and potassium permanganate composite chain initiator, continue stirring at 60°C for 5 hours, and then cool, filter, wash and dry to obtain modified cellulose; wherein the mass ratio of N,N-dimethylacrylamide to cellulose powder is 1:1, the mass ratio of itaconic acid to cellulose powder is 1:3, and the mass ratio of sodium allyl sulfonate to cellulose powder is 1:1.5.
[0052] The preparation method of the intermediate adhesive layer is as follows: adding a photosensitive prepolymer, an active diluent, a titanate coupling agent and a photosensitizer into a mixer, stirring continuously for 3 hours at 40-45° C. to obtain a first mixture, and taking it out for use; taking another mixer, adding modified cellulose and N,N-dimethylformamide into the mixer, mixing and stirring, and heating to 80° C., stirring and reacting continuously at 80° C. for 2 hours to obtain a second mixture; the first mixture and the second mixture are mixed under high-speed stirring at 5000 rpm to obtain an intermediate adhesive, the intermediate adhesive is evenly sprayed on the filler layer and adhered with a high-temperature resistant brown polyimide tape, and the intermediate adhesive layer is formed after the intermediate adhesive is cured, and the peeling strength between the intermediate adhesive layer and the filler layer and the high-temperature resistant brown polyimide tape is higher than the peeling strength between the filler layer and the gold-plated layer, and when the high-temperature resistant brown polyimide tape is torn off, the high-temperature resistant brown polyimide tape can take away the adhesive layer and the filler layer at the same time, and only the filler layer and the gold-plated layer are peeled off.
[0053] The preparation method of the filler layer is as follows: adding gelatin powder to alcohol with a mass fraction of 50% and soaking it for 5 minutes, then heating the gelatin powder in water at 50°C to obtain a first liquid; heating polyurethane to 200°C, keeping it warm and stirring it for 15 minutes to obtain a second liquid; slowly heating low-density polyethylene to 120°C, and fully melting it to obtain a third liquid; at 60°C, uniformly mixing the first liquid, the second liquid, and the third liquid to obtain a mixture; at 30°C, adding nano inorganic fillers, light stabilizers, and dispersants to the mixture, dispersing it at a high speed at 5000 rpm for 10 minutes to obtain a filler layer slurry, and uniformly spraying the filler layer slurry on the gold-plated surface of the incoming copper block of the substrate to form a filler layer.
[0054] The thickness of the filler layer after curing is 0.1 mm.
[0055] The high temperature resistant brown polyimide adhesive is a high temperature resistant brown polyimide tape which takes a polyimide film as a substrate and is coated with a silicone pressure sensitive adhesive on one side, wherein the silicone pressure sensitive adhesive is bonded to a middle adhesive layer.
[0056] The plant cellulose includes cotton cellulose, flax cellulose and ramie cellulose in a mass ratio of 3:1:1.
[0057] The mass ratio of ammonium cerium nitrate to potassium permanganate in the composite chain initiator of ammonium cerium nitrate and potassium permanganate is 4:1.
[0058] The SEM image of the gold-plated surface of the copper block of the substrate material after cleaning the gold-plated surface without using the composite adhesive layer is as follows Figure 1 As shown;
[0059] The SEM image of the gold-plated surface of the substrate copper block with the above-mentioned filler layer sprayed on the gold-plated surface is as follows Figure 2 As shown;
[0060] contrast Figure 1 , Figure 2 It can be seen that the porosity of the gold-plated surface sprayed with the above-mentioned filler layer is significantly reduced, indicating that the filler layer in the present invention has a leveling effect on the gold-plated surface. The leveling in the present invention mainly reduces the surface porosity and maintains the surface flatness visible to the naked eye.
[0061] Example 2
[0062] This embodiment is based on the embodiment 1, and the difference between this embodiment and the embodiment 1 is as follows: In this embodiment, S2.1, preparing a filler layer: using 63 parts of gelatin powder, 21 parts of polyurethane, 5.5 parts of low-density polyethylene, 9 parts of nano inorganic fillers, 2.5 parts of light stabilizers, and 4 parts of dispersants as main raw materials to prepare a filler layer that adheres to the gold-plated surface of the copper block of the substrate and can be peeled off, and the filler layer performs a leveling treatment on the surface of the gold-plated layer by filling the pores on the surface of the gold-plated layer;
[0063] S2.2. Preparation of an intermediate adhesive layer: Using 53 parts of photosensitive prepolymer, 25 parts of modified cellulose, 5.5 parts of titanate coupling agent, active diluent and photosensitizer matching the photosensitive prepolymer as main raw materials, an intermediate adhesive layer adhering to the surface of the filler layer is prepared, wherein the photosensitizer accounts for 4% of the mass of the photosensitive prepolymer.
[0064] Example 3
[0065] This embodiment is based on the embodiment 1, and the difference between this embodiment and the embodiment 1 is as follows: In this embodiment, S2.1, preparing a filler layer: using 65 parts of gelatin powder, 22 parts of polyurethane, 6 parts of low-density polyethylene, 10 parts of nano inorganic fillers, 3 parts of light stabilizers, and 5 parts of dispersants as main raw materials to prepare a filler layer that adheres to the gold-plated surface of the copper block of the substrate and is removable, and the filler layer performs a leveling treatment on the surface of the gold-plated layer by filling the pores on the surface of the gold-plated layer;
[0066] S2.2. Preparation of an intermediate adhesive layer: Using 55 parts of photosensitive prepolymer, 30 parts of modified cellulose, 6 parts of titanate coupling agent, active diluent and photosensitizer matching the photosensitive prepolymer as main raw materials, an intermediate adhesive layer adhering to the surface of the filler layer is prepared, wherein the photosensitizer accounts for 4% of the mass of the photosensitive prepolymer.
[0067] Comparative Example 1
[0068] Based on Example 2, the difference from Example 2 is that the modified cellulose in this comparative example is carboxyl cellulose.
[0069] Comparative Example 2
[0070] Based on Example 2, the difference from Example 2 is that the modified cellulose used in this comparative example is hydroxyethyl cellulose.
[0071] Comparative Example 3
[0072] Based on Example 2, different from Example 2, the modified cellulose in this comparative example uses amphoteric cellulose obtained by a preparation method of homogeneous synthetic betaine-type amphoteric cellulose with application number CN201410309496.0.
[0073] Comparative Example 4
[0074] Based on Example 2, different from Example 2, the filler layer in this comparative example does not contain gelatin powder.
[0075] Comparative Example 5
[0076] Based on Example 2, different from Example 2, the filler layer in this comparative example does not contain polyurethane.
[0077] Comparative Example 6
[0078] Based on Example 2, different from Example 2, the filler layer in this comparative example does not contain low-density polyethylene.
[0079] Comparative Example 7
[0080] Based on Example 2, different from Example 2, this comparative example does not use an intermediate adhesive layer, and directly adheres the high-temperature resistant brown polyimide tape to the filler layer to form a protective layer on the surface of the gold-plated layer.
[0081] Comparative Example 8
[0082] In this comparative example, a high-temperature-resistant brown polyimide tape with a polyimide film as a substrate and coated with a silicone pressure-sensitive adhesive on one side is directly pressed and bonded to the surface of the gold-plated layer to achieve protective treatment of the gold-plated surface of the incoming copper block of the substrate.
[0083] Comparative Example 9
[0084] Based on Example 2, different from Example 2, no modified cellulose is added to the middle adhesive layer of this comparative example.
[0085] Comparative Example 10
[0086] Based on Example 2, different from Example 2, N,N,N-trimethyl-3-(2-methylallylamino)-1-propylammonium chloride is not added to the modified cellulose in this comparative example.
[0087] Comparative Example 11
[0088] Based on Example 2, different from Example 2, N,N-dimethylacrylamide is not added to the modified cellulose in this comparative example.
[0089] Comparative Example 12
[0090] Based on Example 2, different from Example 2, no itaconic acid is added to the modified cellulose in this comparative example.
[0091] Comparative Example 13
[0092] Based on Example 2, different from Example 2, sodium allyl sulfonate is not added to the modified cellulose in this comparative example.
[0093] Comparative Example 14
[0094] Based on Example 2, different from Example 2, the photosensitizer in this comparative example S2.2 is 3% of the mass of the photosensitive prepolymer.
[0095] Comparative Example 15
[0096] Based on Example 2, different from Example 2, the photosensitizer in this comparative example S2.2 is 5% of the mass of the photosensitive prepolymer.
[0097] Comparative Example 16
[0098] Based on Example 2, different from Example 2, the photosensitive prepolymer in this comparative example does not include epoxy soybean oil-based photosensitive prepolymer.
[0099] Comparative Example 17
[0100] Based on Example 2, different from Example 2, the photosensitive prepolymer in this comparative example does not include trifunctional polyurethane acrylate.
[0101] Comparative Example 18
[0102] Based on Example 2, different from Example 2, the photosensitive prepolymer in this comparative example does not include hexafunctional polyurethane acrylate.
[0103] Comparative Example 19
[0104] Based on Example 2, different from Example 2, the thickness of the filler layer after curing in this comparative example is 0.2 mm.
[0105] Test Example 1
[0106] The peel strength between the composite adhesive layer and the gold-plated surface of the copper block of the same substrate, the peeling between the gold-plated layer and the copper block after the composite adhesive layer is peeled off, and the residual adhesive after the composite adhesive layer is peeled off were measured in Examples 1-3, Comparative Examples 4, 5, 6, 7, 8, and 19. The composite adhesive layer in Comparative Example 8 is a single-layer high-temperature resistant brown polyimide tape, and the results are shown in Table 1.
[0107] The testing method of the peel strength between the composite adhesive layer and the gold-plated surface of the copper block of the same substrate is as follows: 180° peeling is performed using an electronic peeling tester, and a copper plate having a composite adhesive layer formed by a filler layer, an intermediate adhesive layer, and a high-temperature resistant brown polyimide tape adhered to the gold-plated surface is clamped on the electronic peeling tester, and the peeling force of the composite adhesive layer from the gold-plated surface is measured by pulling the high-temperature resistant brown polyimide tape, and the peeling force is the peeling force of the filler layer from the gold-plated surface.
[0108] The peeling condition between the gold-plated layer and the copper block after the filler layer is peeled off: directly observe whether the gold-plated layer on the copper block is damaged by falling off, cracking, etc. after the composite adhesive layer is peeled off from the gold-plated surface.
[0109] Residual glue after the filler layer is peeled off: Directly observe and touch the surface of the gold-plated layer. If there is no residue on the surface of the gold-plated layer and it does not feel sticky when touched, it means there is no residual glue. Otherwise, there is residual glue.
[0110] Table 1 Peel test of packing layer
[0111]
[0112] In Comparative Example 7, no intermediate adhesive layer is used, and the high-temperature resistant brown polyimide tape is directly adhered to the filler layer to form a protective layer on the surface of the gold-plated layer. When the high-temperature resistant brown polyimide tape is torn off from the gold-plated layer, the high-temperature resistant brown polyimide tape is separated from the filler layer, and the filler layer is not torn off synchronously with the brown polyimide tape. After the brown polyimide tape is torn off, the filler layer is still adhered to the gold-plated layer; this indicates that when no intermediate adhesive layer is used, the peel strength between the high-temperature resistant brown polyimide tape and the filler layer is less than the peel strength between the filler layer and the gold-plated layer.
[0113] Examples 1-3 all have enhanced peel strength, and have relatively high bonding strength without residual glue after peeling. Compared with the prior art (Comparative Example 8), the bonding strength between the brown polyimide tape and the gold-plated layer is improved, which has the effect of strengthening the brown polyimide tape to prevent it from falling off.
[0114] The composite adhesive layers in Examples 1-3 of the present invention are all peeled off as a whole, indicating that the peeling strength between the intermediate adhesive layer and the filler layer, and between the intermediate adhesive layer and the high-temperature resistant brown polyimide tape in the composite adhesive layer of the present invention are higher than the peeling strength between the filler layer and the gold-plated layer. When the high-temperature resistant brown polyimide tape is torn off, the high-temperature resistant brown polyimide tape can take away the adhesive layer and the filler layer at the same time, thereby realizing the one-time overall peeling of the composite adhesive layer.
[0115] Test Example 2
[0116] The peel strengths of the filler layers and the intermediate adhesive layers prepared in Examples 1-3, Comparative Examples 1-6, and 9-19 were measured. The results are shown in Table 2.
[0117] The determination method is as follows: the intermediate adhesive layer is adhered to the substrate by spraying, the intermediate adhesive layer is tightly bonded to the substrate, and then the filler layer is sprayed on the intermediate adhesive layer. After complete curing, the filler layer forms a rubber layer with a certain flexibility on the surface of the intermediate adhesive layer. Then, the peeling force between the filler layer and the intermediate adhesive layer is determined by the peeling force test method in Test Example 1 and the peeling condition is observed. The minimum force for the filler layer to be peeled off from the intermediate adhesive layer is the peeling force between the filler layer and the intermediate adhesive layer. The results are shown in Table 2.
[0118] Table 2 Peel strength test results of filler layer and middle adhesive layer
[0119]
[0120] Compared with the above data, the peeling force between the intermediate adhesive layer and the filler layer in Comparative Example 9 without adding modified cellulose is smaller than the peeling force between the filler layer and the gold-plated layer. When peeling the entire composite adhesive layer, the intermediate adhesive layer in Comparative Example 9 has a higher risk of separation between the intermediate adhesive layer and the filler layer. The higher the peeling force between the intermediate adhesive layer and the filler layer, the better the integrity of the two.
[0121] Test Example 3
[0122] The peeling force and peeling conditions between the intermediate adhesive layer prepared in Examples 1-3, Comparative Examples 1-3, and 9-18 and the high temperature resistant brown polyimide tape were measured. The results are shown in Table 3. The test method refers to the peeling force test method in Test Example 1.
[0123] Table 3 Peel force test results between the middle adhesive layer and the high temperature resistant brown polyimide tape
[0124]
[0125] In Examples 1-3 of the present invention, the peeling force between the middle adhesive layer and the high temperature resistant brown polyimide tape is greater than the peeling force between the filler layer and the surface of the gold-plated layer. When the composite adhesive layer and the gold-plated layer are peeled off, the middle adhesive layer and the high temperature resistant brown polyimide tape will not separate. The overall model. Combining the data in Tables 1, 2, and 3, it can be seen that Example 2 of the present invention is the best ratio.
[0126] The above description is only a preferred embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions and improvements made by any technician familiar with the field within the spirit and principle of the present invention should be included in the scope of protection of the present invention.
Claims
1. An enhanced ball grid array packaging process, comprising protective treatment of the gold-plated surface of a substrate copper block, characterized in that: The protective treatment of the gold-plated surface of the substrate copper block is achieved by the following specific steps: S1. Clean the gold-plated surface of the incoming copper block of the substrate; S2. A composite adhesive layer formed by a filler layer, an intermediate adhesive layer, and a high-temperature resistant brown polyimide tape is used to protect the gold-plated surface of the copper block of the substrate after the dust removal treatment. The specific steps are as follows: S2.1, preparing a filler layer: using 63 parts of gelatin powder, 21 parts of polyurethane, 5.5 parts of low-density polyethylene, 9 parts of nano inorganic filler, 2.5 parts of light stabilizer, and 4 parts of dispersant as main raw materials to prepare a filler layer that adheres to the gold-plated surface of the copper block of the substrate and can be peeled off, and the filler layer performs a leveling treatment on the surface of the gold-plated layer by filling the pores on the surface of the gold-plated layer; S2.2, prepare the intermediate adhesive layer: use 53 parts of photosensitive prepolymer, 25 parts of modified cellulose, 5.5 parts of titanate coupling agent, active diluent and photosensitizer matching the photosensitive prepolymer as main raw materials to prepare the intermediate adhesive layer adhering to the surface of the filler layer, wherein the photosensitizer is 4% of the mass of the photosensitive prepolymer; the photosensitive prepolymer includes epoxy soybean oil-based photosensitive prepolymer, trifunctional polyurethane acrylate, hexafunctional polyurethane acrylate, and the mass ratio of the epoxy soybean oil-based photosensitive prepolymer, trifunctional polyurethane acrylate, and hexafunctional polyurethane acrylate is 1.5:0.5:1; the photosensitizer is 1-hydroxycyclohexyl benzophenone and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, and the mass ratio of 1-hydroxycyclohexyl benzophenone and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide is 2:1; the active diluent is polyethylene glycol diacrylate; S2.
3. First spray a filler layer on the gold-plated surface of the copper block of the substrate material. After air-drying at room temperature for 10 minutes, spray an intermediate adhesive layer on the surface of the filler layer. Then use a 200W ultraviolet lamp with a wavelength of 365nm to irradiate the intermediate adhesive layer for 6 minutes. After 6 minutes, press and adhere the high-temperature resistant brown polyimide tape to the intermediate adhesive layer. Continue to air-dry at room temperature for 30-40 minutes. The filler layer, the intermediate adhesive layer, and the high-temperature resistant brown polyimide tape are sequentially adhered to form a composite adhesive layer to complete the protective treatment of the gold-plated surface of the copper block of the substrate material.
2. The enhanced ball grid array packaging process according to claim 1, characterized in that: The preparation method of the modified cellulose is: A. placing plant cellulose in a 10% by mass sodium hydroxide solution for alkalization for 5 hours to obtain alkalized cellulose, and then drying the alkalized cellulose in an oven at 65° C. for 10 hours and then grinding the cellulose to obtain cellulose powder; B. Add cellulose powder to deionized water, pass nitrogen protection, heat to 40°C and stir at constant temperature for 20 minutes, then add ammonium persulfate (1% by weight of cellulose powder), continue to heat under stirring, and slowly drip N,N,N-trimethyl-3-(2-methylallylamino)-1-propylammonium chloride after heating to 50°C. After stirring at constant temperature of 50°C for 3.5 hours, adjust the pH of the product to neutral, and then filter, wash and dry to obtain the first intermediate product; wherein the mass ratio of N,N,N-trimethyl-3-(2-methylallylamino)-1-propylammonium chloride to cellulose powder is 1:1.5; C. Add the first intermediate product to a 5% by mass sodium hydroxide solution, mix evenly, heat to 50°C, slowly add N,N-dimethylacrylamide at 50°C, continue stirring, heat to 60°C, and stir at a constant temperature for 2 hours. After 2 hours, add itaconic acid and sodium allyl sulfonate and continue stirring, keep the temperature of the reaction system at 60°C, continue stirring for 30 minutes, slowly add ammonium cerium nitrate and potassium permanganate composite chain initiator, continue stirring at 60°C for 5 hours, and then cool, filter, wash and dry to obtain modified cellulose; wherein the mass ratio of N,N-dimethylacrylamide to cellulose powder is 1:1, the mass ratio of itaconic acid to cellulose powder is 1:3, and the mass ratio of sodium allyl sulfonate to cellulose powder is 1:1.
5.
3. The enhanced ball grid array packaging process according to claim 1, characterized in that: The preparation method of the intermediate adhesive layer is as follows: adding a photosensitive prepolymer, an active diluent, a titanate coupling agent and a photosensitizer into a mixer, stirring continuously for 3 hours at 40-45° C. to obtain a first mixture, and taking it out for use; taking another mixer, adding modified cellulose and N,N-dimethylformamide into the mixer, mixing and stirring, and heating to 80° C., stirring and reacting continuously at 80° C. for 2 hours to obtain a second mixture; the first mixture and the second mixture are mixed under high-speed stirring to obtain an intermediate adhesive, the intermediate adhesive is evenly sprayed on the filler layer and adhered with a high-temperature resistant brown polyimide tape, and the intermediate adhesive layer is formed after the intermediate adhesive is cured, and the peel strength between the high-temperature resistant brown polyimide tape and the intermediate adhesive layer, and the peel strength between the intermediate adhesive layer and the filler layer are both higher than the peel strength of the filler layer on the gold-plated layer.
4. The enhanced ball grid array packaging process according to claim 1, characterized in that: The nano inorganic filler in the filler layer is nano silicon dioxide, the light stabilizer is nano titanium dioxide, and the dispersant is sodium dodecyl sulfate.
5. The enhanced ball grid array packaging process according to claim 4, characterized in that: The preparation method of the filler layer is as follows: adding gelatin powder to alcohol with a mass fraction of 50% and soaking it for 5 minutes, then heating the gelatin powder in water at 50°C to obtain a first liquid; heating polyurethane to 200-230°C, and stirring it for 10-15 minutes to obtain a second liquid; slowly heating low-density polyethylene to 120-140°C, and fully melting it to obtain a third liquid; at 60°C, uniformly mixing the first liquid, the second liquid, and the third liquid to obtain a mixture; at 30°C, adding nano inorganic fillers, light stabilizers, and dispersants to the mixture, and dispersing it at a high speed at 5000 rpm for 10 minutes to obtain a filler layer slurry, and uniformly spraying the filler layer slurry on the gold-plated surface of the incoming copper block of the substrate to form a filler layer.
6. The enhanced ball grid array packaging process according to claim 5, characterized in that: The thickness of the filler layer after curing is 0.1 mm.
7. The enhanced ball grid array packaging process according to claim 1, characterized in that: The high temperature resistant brown polyimide adhesive is a high temperature resistant brown polyimide tape which takes a polyimide film as a substrate and is coated with a silicone pressure sensitive adhesive on one side, wherein the silicone pressure sensitive adhesive is bonded to a middle adhesive layer.
8. The enhanced ball grid array packaging process according to claim 2, characterized in that: The plant cellulose includes cotton cellulose, flax cellulose and ramie cellulose in a mass ratio of 3:1:
1.
9. The enhanced ball grid array packaging process according to claim 2, characterized in that: The mass ratio of ammonium cerium nitrate to potassium permanganate in the composite chain initiator of ammonium cerium nitrate and potassium permanganate is 4:1.
Citation Information
Patent Citations
A preparation method for homogeneously synthesizing betaine-type amphoteric cellulose
CN104045771B
High-temperature-resistant polyimide adhesive tape
CN113045997A
Plastic-based gold stamping film with high salt water resistance and preparation method of plastic-based gold stamping film
CN117565594A